Acute respiratory infections (ARIs) and factors associated with their poor clinical outcome among children under-five years attending pediatric wards of public hospital in Southwest district of Ethiopia: A prospective observational cohort study. (7th November 2022) - Abayneh, Mengistu; Muleta, Dassaleng; Simieneh, Asnake; Duguma, Tadesse; Asnake, Molla; Teressa, Murtii; Endalkachew, Biruk; Toru, Milkiyas
This study was designed to assess the prevalence and factors associated with poor clinical outcome of acute respiratory infections (ARIs) among children less than five years of age at Mizan-Tepi university teaching public hospital in southwest district of Ethiopia. A prospective observational cohort study design was conducted from 01 June to August 30, 2020. Data related to socio-demographics, child nutritional status, clinical and environmental characteristics of patients were collected with structured questionnaire. Follow-up data were gathered from patient's medical records using standard data collection tool. The data were analyzed using SPSS versions 25.0. In this study, 305 children of age less than five years were included. Of these, 124 (40.7%) of children were diagnosed with ARIs, of which 66 (53.2%) were female and 69 (55.6%) were age of 24–59 months. Of children diagnosed with ARIs, 21 (16.9%) were ended with poor clinical outcomes after completion of their treatment. In the multivariate analysis, age of children and presence of any other disease conditions (OR = 0.331; 95% CI: 0.123– 0.880; p = 0.024), exposure to indoor air pollution (OR = 0.344; 95% CI: 0.128– 0.925; p = 0.030),   malnutrition (OR = 0.175; 95% CI: 0.058– 0.523; p = 0.002) and end point pneumonia (OR = 0.305; 95% CI: 0.113–0.821; p = 0.015) were found to be independent factors for poor outcome of under-five children with ARIs. Our findings highlight that timely detection, proper management and treatments as well as addressing other contributing factors are essentials in order to reduce prevalence and poor clinical outcomes of under five children with ARIs.